Seismic Response and Evaluation of SDOF Self-Centering Friction Damping Braces Subjected to Several Earthquake Ground Motions - Jong Wan Hu; Myung-Hyun Noh (Advances in Materials Science and Engineering)
This paper mainly deals with seismic response and performance for self-centering friction damping braces (SFDBs) subjected to several maximum- or design-leveled earthquake ground motions. The self-centering friction damping brace members consist of core recentering components fabricated with superelastic shape memory alloy wires and energy dissipation devices achieved through shear friction mechanism. As compared to the conventional brace members for use in the steel concentrically braced frame structure, these self-centering friction damping brace members make the best use of their representative characteristics to minimize residual deformations and to withstand earthquake loads without member replacement. The configuration and response mechanism of self-centering friction damping brace systems are firstly described in this study, and then parametric investigations are conducted through nonlinear time-history analyses performed on numerical single degree-of-freedom spring models. After observing analysis results, adequate design methodologies that optimally account for recentering capability and energy dissipation according to their comparative parameters are intended to be suggested in order to take advantage of energy capacity and to minimize residual deformation simultaneously.